Expanding experiential learning opportunities to alumni for the development of job-search skills: a case in a Peruvian university - Olivos, Mariella (2020)
At Universidad ESAN in Lima, Peru, a blended workshop using videoconferencing technology, online forums and minimal local class discussions was carried out through the Global Partners in Education (GPE) network from August to November 2017. The workshop was voluntary and facilitated interaction between Peruvian students and students from the US, Mexico, and China over the course of three modules. The participants from Peru were a heterogeneous group consisting of undergraduates and recent graduates, some pre-professional participants and some who were already working. Upon completion of each module, they were surveyed regarding their perspectives on this international virtual experience and how it could positively impact their professional lives. The students' diverse perspectives shed light on the ways in which intercultural interaction via information and communications technology (ICT) can be used to increase participants’ future professional success due to the principles of acquiring new skills and improving employability.